Tantangan dan Peluang Konservasi di Kalimantan (Studi Kasus Arwana Super Red) - Arfah Syam, Muh. (Journal of Comprehensive Science, 2025)
The Super Red Arowana (Scleropages formosus) is a highly valuable ornamental fish species with significant ecological, economic, and cultural importance, especially in the Kalimantan region. Known for its vibrant red coloration, the Super Red Arowana is one of Indonesia’s key export commodities in international markets. However, high demand for this species has led to serious threats to its sustainability in the wild, including overfishing and habitat destruction caused by deforestation and infrastructure development. This study aims to analyze the ecological, economic, and social characteristics of the Super Red Arowana, as well as assess the current population status and conservation efforts. The findings indicate that the population of Super Red Arowana in the wild has significantly declined, despite regulatory measures such as those enforced by CITES. While breeding programs and the establishment of conservation areas have been implemented, challenges such as weak law enforcement and a lack of public awareness continue to hinder effective conservation efforts. This study provides policy recommendations focused on strengthening trade regulations, protecting habitats, and increasing public awareness through education and the development of conservation-based ecotourism. With appropriate interventions, the wild population of Super Red Arowana could gradually recover, ensuring that this species remains an integral part of Indonesia's biodiversity.